Preparing principals to raise student achievement : implementation and effects of the New Leaders program in ten districts - Gates, Susan M., 1968-; Hamilton, Laura S., 1968-; Martorell, Francisco; Burkhauser, Susan; Heaton, Paul.; Pierson, Ashley; Baird, Matthew; Vuollo, Mirka; Li, Jennifer J.; Lavery, Diana Catherine; Harvey, Melody; Gu, Kun.; et al. (Santa Monica, CA : RAND, 2014)
New Leaders is a nonprofit organization with a mission to ensure high academic achievement for all students by developing outstanding school leaders to serve in urban schools. Its premise is that a combination of preparation and improved working conditions for principals, especially greater autonomy, would lead to improved student outcomes. Its approach involves both preparing principals and partnering with school districts and charter management organizations (CMOs) to improve the conditions in which its highly trained principals work. As part of the partnerships, New Leaders agrees to provide carefully selected and trained principals who can be placed in schools that need principals and to provide coaching and other support after those principals are placed. The districts and CMOs agree to establish working conditions that support, rather than hinder, the principals$1 (Befforts to improve student outcomes. This report describes how the New Leaders program was implemented in partner districts, and it provides evidence of the effect that New Leaders has on student achievement.s
"RAND Education."
Includes bibliographical references (p. 111-118).
"Sponsored by New Leaders."
Also available on the internet via WWW in PDF format.
Description based on print resource.
Keywords: Educational leadership -- United States; Academic achievement -- United States; School management and organization -- United States; School improvement programs -- United States; Educational innovations -- United States; Electronic books